TEMPERATURE OBSERVATIONS IN THE WATER-OFF MUARA KARANG - Kastoro, -; Birowo, Soejatno (Marine Research in Indonesia, 1977)
During the period of March 1975 to February 1976 a survey was carried out in the water off Muara Karang, Jakarta Bay. Water temperature were slightly higher than those in the open sea, and showed a seasonal variation. The seasonal variation axe affected by meteorological conditions, incoming water from neighbouring seas, and by the land mass.